Neurocognitive outcome after coronary artery bypass surgery using minimal versus conventional extracorporeal circulation: a randomised controlled pilot study. Issue 13 (28th February 2011) - Anastasiadis, Kyriakos; Argiriadou, Helena; Kosmidis, Mary H; Megari, Kalliopi; Antonitsis, Polychronis; Thomaidou, Evanthia; Aretouli, Eleni; Papakonstantinou, Christos
Abstract : Objective: Neurocognitive impairment can be a debilitating complication after cardiac surgery. The aim of this study was to assess the effect of minimal extracorporeal circulation (MECC) versus conventional extracorporeal circulation (CECC) on neurocognitive function after elective coronary artery bypass grafting (CABG) and whether this can be attributed to improved cerebral perfusion intraoperatively. Methods and results: 64 patients scheduled for elective CABG surgery were prospectively randomly assigned to surgical revascularisation with MECC versus CECC. All patients were continuously monitored for changes in cerebral oxygenation with near-infrared spectroscopy during the procedure. Neurocognitive assessment was performed before surgery, on the day of discharge and at 3 months postoperatively using a battery of standardised neurocognitive tests. Both groups were comparable in terms of demographic and clinical data. MECC was associated with improved cerebral perfusion during cardiopulmonary bypass (CPB). Eleven patients operated on with MECC and 17 with CECC experienced at least one episode of cerebral desaturation (38% vs 55%, p=0.04) with similar duration (10 vs 12.3 min, p=0.1). At discharge patients operated on with MECC showed a significantly improved performance on complex scanning, visual tracking, focused attention and long-term memory. At 3 months significantly improved performance was also evident on visuospatial perception, executive function, verbal working memory and short-term memory. Patients operated on with MECC experienced a significantly lower risk of early cognitive decline both at discharge (41% vs 65%, p=0.03) and at 3-month evaluation (21% vs 61%, p<0.01). Conclusions: Use of MECC attenuates early postoperative neurocognitive impairment after coronary surgery compared with conventional CPB. This finding may have important implications on the surgical management strategy for coronary artery disease. Clinical trial registration number: The study is registered at ClinicalTrials.gov, number NCT01213511 .